ANALYSIS 0F LEADERSHIP ROLE: EVIDENCE FROM INDUSTRIES IN MANADO - Eman, Trivena Deyvi; Pangemanan, Sifrid S. (Universitas Sam Ratulangi, 2018)
Abstract: In industries Manado personal characteristics of the leaders determine leadership role.This research is all about identifying factors affecting the workers’ perception of an Leadership role at An industries in Manado. These industries ranging from PT Astra Isuzu International Manado (Car distributor), Multimart (Retail), Girsafotocopy and print (Printing service) and WarungBendito (Restaurant).This research is categorized as causal research. Causal research is quantitative and structured in design. Causal research differs in its attempt to explain the cause and effect relationship between variables. This research is conducted in Manado, North Sulawesi during the first semester of 2018. Since this study entirely uses primary data which obtained via questionnaire to the 230 samples, this research is categorized as a field research. Statistical result shows that task assignment and personal characteristic does not significantly affect Leadership Role of leaders in various industries in Manado. It means, how managers or leaders delegate task does not determine the character of the leaders themselves, whether it is positive or negative. The companies across Manado should pay attention to the findigs, Good leading character of a leader will strengther the leader’s relationship with employee which could create a better work environment.Keyword: effective leadership, task assignment, personal characteristics, professional characteristics, attitude